Measuring Driver's Perceived Workload Using Fractal Dimension of Pupil Dilation. (December 2020) - Kim, Jung Hyup; Yang, Xiaonan
Many physiological measures have been proposed for quantifying the workload in a driving environment. Among them, pupillary response has been identified as an effective workload indicator that can be measured less intrusively and without disrupting the worker's ongoing activities. The purpose of this study is to investigate the fractal dimension of pupil dilation (FDPD) to measure perceived workload in a driving simulation environment. For the experiment, two different driving scenarios were developed and tested by using the OpenDS driving simulator. The results demonstrate that one of the scenarios shows a significant negative correlation between FDPD and the perceived workload outcome from NASA-Task Load Index (TLX) questionnaires.